Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1073/pnas.1418690112
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptides catalyze rapid peptide exchange on MHC class I molecules

Abstract: Peptide ligand selection by MHC class I molecules, which occurs by iterative optimization, is the centerpiece of immunodominance in antiviral and antitumor immune responses. For its understanding, the molecular mechanisms of peptide binding and dissociation by class I molecules must be elucidated. To this end, we have investigated dipeptides that bind to the F pocket of class I molecules. We find that they accelerate the dissociation of prebound peptides of both low and high affinity, suggesting a mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 30 publications
2
55
0
Order By: Relevance
“…Thus, ERAP2 might be particularly relevant in the context of low activity ERAP1 variants. A third possibility is that, since ERAP2 efficiently degrades 8-mers and shorter peptides, it might influence in this way the substrate-inhibition kinetics of ERAP1 trimming (20,38) or the affinity-dependent peptide exchange on the MHC-I molecule mediated by very small peptides (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ERAP2 might be particularly relevant in the context of low activity ERAP1 variants. A third possibility is that, since ERAP2 efficiently degrades 8-mers and shorter peptides, it might influence in this way the substrate-inhibition kinetics of ERAP1 trimming (20,38) or the affinity-dependent peptide exchange on the MHC-I molecule mediated by very small peptides (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…To test whether the K22-D35 loop of TAPBPR was a functionally important region for mediating peptide selection, we first replaced all the residues in the loop with either glycine, alanine or serine, to produce a TAPBPR variant with a potentially functionless loop (TAPBPR Øloop )( Table 1). More subtle mutations of this loop were designed based on the work by Springer and colleagues, who demonstrated that dipeptides carrying long hydrophobic residues are able to bind to the peptide-binding groove of recombinant MHC I and enhance peptide dissociation [15]. Thus, we explored whether a leucine residue at position 30 of the mature TAPBPR protein, the only long hydrophobic residue within the entire loop, was involved in peptide exchange on MHC I.…”
Section: Tapbpr Loop Mutants Are Stably Expressed and Bind Mhc I And mentioning
confidence: 99%
“…The plate was incubated overnight at 37 °C with 5% CO 2 before the cells were transferred to 96-well U-bottomed plates and spun at 2000 rpm for 2 min. The cells were washed twice with PBS and lysed with 100 μl lysis buffer containing PBS with 0.5% Nonidet P40 (Sigma-Aldrich) and 0.15 mM Chlorophenol Red-ß-D-galactopyranoside (Sigma-Aldrich)26. The assay was incubated for a further 6 h at room temperature with absorbance readings at 570 nm recorded every 10 min in an Infinite Pro M200 plate reader (Tecan).…”
Section: Methodsmentioning
confidence: 99%